PENGARUH MOTIVASI KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KEPUASAN KERJA (STUDI PADA RSUD BAHTERAMAS PROVINSI SULAWESI TENGGARA) - Asni Satriawati; Sudirman Zaid; Yusuf (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine the effects of work motivation and work-life balance on employee performance, with job satisfaction serving as a mediating variable, at Bahteramas Regional General Hospital, Southeast Sulawesi Province. A quantitative research approach was employed involving all 88 employees as the research sample using a census technique. Data were collected through a structured questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The findings reveal that work motivation, work-life balance, and job satisfaction each have a positive and significant effect on employee performance. Furthermore, job satisfaction significantly mediates the relationships between work motivation and employee performance, as well as between work-life balance and employee performance. These results indicate that enhancing employees' motivation, maintaining a healthy work-life balance, and improving job satisfaction contribute to better employee performance and higher-quality healthcare services.